Determinants of Aggression in Non-Urban Sumatra: Age, Handedness, and Regional Context - Putri, Isnaini Anggraini; Badriah, Nur; Muktiono, Permesyawari; Mulyana, Jeane Siswitasari; Maretta, Gres; Nurhayu, Winati; Darmawan, Andy (UIN Sunan Gunung Djati, 2026)
This study aims to analyze regional variation in aggressiveness in non-urban areas of Sumatra and to examine the simultaneous influence of demographic, biological, and regional factors on individual aggression levels. This study is important because comparative quantitative research across regions in Indonesia, particularly outside urban contexts, remains limited, even though aggression directly relates to social dynamics and regional violence risks. The study employs a quantitative approach with a cross-sectional design. The researchers collected data from 610 respondents aged 14–87 years in Simalungun Regency (North Sumatra), as well as South Lampung, Way Kanan, and Central Lampung, using convenience sampling. The researchers measured aggressiveness using the Buss–Perry Aggression Questionnaire (BPAQ) and analyzed the data through Kendall’s correlation and multiple linear regression. The findings show a mean aggressiveness score of 2.815 (on a 1–5 scale), with the verbal subscale recording the highest score. The regression model explains 7.6 % of the variance in aggression and identifies four significant predictors: Simalungun region, age (negatively correlated), left-handedness, and Lampung ethnicity. Sex, income, and birth order do not demonstrate significant effects. These findings indicate that aggression is shaped more strongly by developmental factors, biological proxies, and sociocultural and regional dynamics than by economic factors alone. This study implies the importance of regionally and culturally based interventions to strengthen emotional regulation, particularly among young populations in areas with higher aggression scores. In terms of originality, this study represents the first comparative quantitative research that integrates regional, ethnic, and handedness variables within a single regression model in a non-urban Sumatran context, thereby providing empirical and methodological contributions to locally grounded social policy development.